Evaluasi Dan Peninjauan Stabilitas Lereng Menggunakan Program Software Geoslope Pada Area Permukiman Di Bawah Lereng Desa Ngrimbi, Kecamatan Bareng, Kabupaten Jombang - Susanto, Muhammad Angga Aris (Universitas Negeri Surabaya, 2023)
The slope is an inclined plane area that connects other planes that have different elevations. Each slope has the possibility of landslides. According to SNI 8470-2017 regulations landslides can occur if the safety factor does not meet the Safety Factor (SF <1.5). The slopes in one of the Jombang districts, to be precise in one Ngrimbi Village, Bareng District, tend to have poor soil and landslides can occur, so a slope stability analysis is needed. In this study, the authors conducted an evaluation and review of slope stability in residential areas under the slopes of Ngrimbi Village, Bareng District, Jombang Regency to determine the slope safety factor (SF) value using the Geoslope 2023 software program. Soil data used in this study used the Geoslope 2023 software program. parameters liquid limit value (LL) = 35%, 45%, and 50% obtained from soil data from previous research literature studies. The data is connected or correlated to obtain values of the soil shear angle (?) and soil cohesion (c). The results of this study obtained slope stability at Liquid Limit (LL) 35% (SF) = 1.224 < 1.5 (Unsafe), Liquid Limit (LL) 45% (SF) = 1.043 < 1.5 (Unsafe) and Liquid Limit (LL) 50% (SF) = 0.976 < 1.5 (Not safe).